Досвід країн Європейського Союзу з відбору в поліцію (на прикладі Литовської Республіки) - Гарбузюк, К. Г.; Harbuziuk, K. H. (Науковий вісник публічного та приватного права. - 2019. - Вип. 3, т. 1. - С. 116-121, 2019)
Досліджено досвід Литовської Республіки щодо відбору поліцейських на службу. Особливу увагу звернено на технологічний рівень відбору на державну службу, для чого спеціально впроваджено електронний сервіс, за допомогою якого можна подати документи для участі в конкурсах, що використовується державними службовцям без спеціальних звань у поліції, де також: перелічені відео уроки з тестування; подано інформацію про перевірку рівня компетентності з іноземної мови; зроблено альтернативні оголошення про вакантні посади; наведені зразки тестувань.

In the article, based on the analysis of scientific literature, the experience of the Republic of Lithuania in the selection of police officers for service is explored. Particular attention was paid to the technological level of selection for the civil service, which specifically introduced an electronic service through which to submit documents for participation in competitions, which are used by public servants without special ranks in the police, which also includes: video testing lessons; information on verification of the level of competence in a foreign language is provided; alternative vacancy announcements have been made; test samples are provided. It is emphasized that in the Republic of Lithuania persons wishing to serve in the police, apply to the territorial police authority at the place of residence, where you can decide on an educational institution, fill out or provide in advance prepared documents. The same body organizes: a medical examination by an appropriate health panel for suitability; verification of compliance with the requirements of general physical training; examination for the presence of a court sentence, prosecution, etc. It is determined that the personnel selection policy is implemented by the personnel council of the Police Department of the Ministry of Internal Affairs of the Republic of Lithuania. The analysis of the legislation of this country suggests that the requirements for the candidate are conditioned by the future profession of police officer. The peculiarity of the legal regulation of the selection institution for the police is the application of the said statute, which established basic requirements not only for police officers but also for employees of other MIA bodies. It is concluded that in the Republic of Lithuania disputes regarding admission to internal service and admission to vocational schools are resolved in accordance with the law. In order to increase the technological level of selection for the civil service, an electronic service has been specially introduced, with the help of which it is possible to submit documents for participation in competitions used by public servants without special ranks in the police, which also include: video testing lessons; information on verification of level of competence in a foreign language is provided; alternative vacancy announcements have been made; test samples are provided.

Исследован опыт Литовской Республики по отбору полицейских на службу. Особое внимание обращено на технологический уровень отбора на государственную службу, для чего специально внедрен электронный сервис, с помощью которого можно подать документы для участия в конкурсах, используемых государственными служащими без специальных званий в полиции, где: перечислены видео уроки по тестированию; представлена ​​информация о проверку уровня компетентности по иностранному языку; сделаны альтернативные объявления о вакантных должностях; приведены образцы тестирований.
Keywords: зарубіжний досвід; foreign experience; зарубежный опыт; Національна поліція України; National Police of Ukraine; Национальная полиция Украины; поліція; police; полиция; Литовська Республіка; Republic of Lithuania; Литовская Республика; відбір в поліцію; selection to the police; отбор в полицию